Information Security Awareness Among Employees of a Private Financial Organization: Case from Misurata, Libya (Journal of Academic Research, 2024)
Banks rely heavily on information security to safeguard their critical data and infrastructure. Because employees can be vulnerable to cyber threats, it's crucial to educate and train them to mitigate these risks. This study investigated information security awareness among Libyan bank employees in Misrata City using the Knowledge, Attitude, Behavior (KBA) model. It explored how knowledgeable employees are about information security and what factors influence their awareness. Researchers surveyed a group of employees using a questionnaire that assessed their knowledge, attitude, and behavior towards information security. The results revealed a positive correlation between employee awareness and the importance of information security. Interestingly, password management was the one area where employees showed a lack of awareness. The study recommends developing a national information security strategy for banks, alongside ongoing training programs for employees.